Digital Leadership of School Administrator Affecting Learning Management the 21st Century of teachers Under the Pathum Thani Secondary Education Service Area Office - Seehabunjan, Patimawadee; Phattharakul, Weeraphat; Montaisong, Teerawat (Mahachula Academic Journal, 2023)
The purposes of this research were to study: (1) digital leadership of school administrators under the Pathum Thani Secondary Education Service Area Office (2) learning management in the 21st Century of teachers under the Pathum Thani Secondary Education Service Area Office, and (3) the digital leadership of school administrator affecting learning management in the 21st Century of teachers. The samples were 314 teachers of The Pathum Thani Secondary Education Service Area Office, selected by using stratified sampling. The research instrument used was a questionnaire with the reliability of 0.98. The results of the research indicate that (1) the digital leadership of school administrators is at high level. When considering each aspect, the highest average aspect is the digital vision, followed by the digital communication. The lowest average aspects are the digital Professionalism. (2) The learning management in the 21st Century of teachers are at high level. When considering each aspect, the highest average aspect is the design of learning management, followed by learning management. The lowest average aspect is the development of media technology and educational information systems. (3) The relationship between digital leadership of school administrators and learning management in the 21st Century of teachers is positively related overall at a moderate level. The highest relationship is digital vision and development of media technology and educational information systems, digital learning culture and design of learning management, and digital learning culture and learning management. The digital leadership of school administrator affecting learning management in the 21st Century of teachers is the digital learning culture, the digital communication, and the digital vision at a significantly statistical level of .05.